Reach and engagement on the history of nursing on social media in light of Pierre Lévy - Natália Maria Freitas e Silva Maia; Agostinho Antônio Cruz Araújo; Ana Maria Ribeiro dos Santos; Rafaela Siqueira Costa Schreck; Maria Angélica de Almeida Peres; Fernanda Batista Oliveira Santos (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To analyze the reach and engagement on the history of nursing on social media of the Memory Center of the School of Nursing, Federal University of Minas Gerais (CEMENF/UFMG), in light of Pierre Lévy. Methods: Documentary study carried out on CEMENF’s Instagram and on the YouTube of the School of Nursing of UFMG, from September to December 2021. The findings were analyzed according to Pierre Lévy’s concepts. Results: Publications on social media, in the years 2020 and 2021, resulted in an average of 6.79 feed posts and 1.42 Reels on Instagram, with an average of 25.54 comments on feed posts and 512.17 views on Reels. As for YouTube, an average of 1.58 posts was observed, with 2164.08 views and 101.58 likes. Conclusions: Cyberspace can be a powerful instrument for bringing university museums closer to society and for disseminating extension and research projects.